2020
DOI: 10.3892/etm.2020.9045
|View full text |Cite|
|
Sign up to set email alerts
|

miR‑29b enhances the proliferation and migration of bone marrow mesenchymal stem cells in rats with castration‑induced osteoporosis through the PI3K/AKT and TGF‑β/Smad signaling pathways

Abstract: The aim of the present study was to investigate the role of microRNA (miR)-29b in the proliferation and migration of bone marrow mesenchymal stem cells (BMSCs) in rats with castration-induced osteoporosis and the relevant mechanisms. The gene expression profiling microarray technique was utilized to sequence the BMSCs with overexpressed miR-29b. The intersection of the potential targets and the genes downregulated in the sequencing were utilized for GO enrichment analysis. Gene set enrichment analysis (GSEA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…miR-29b may be associated with the regulation of osteogenic and osteolytic differentiation in aseptic inflammation of the bone [ 115 ]. Recent studies found that first miR-29b can promote proliferation and migration of rat bone marrow MSCs through PI3K/AKT and TGF- β /Smad signaling pathways [ 116 ]. These protective effects seen in inflammatory bone diseases may be related to the osteoblast-osteoclast dynamic balance, but further research is needed to elucidate the exact mechanisms.…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…miR-29b may be associated with the regulation of osteogenic and osteolytic differentiation in aseptic inflammation of the bone [ 115 ]. Recent studies found that first miR-29b can promote proliferation and migration of rat bone marrow MSCs through PI3K/AKT and TGF- β /Smad signaling pathways [ 116 ]. These protective effects seen in inflammatory bone diseases may be related to the osteoblast-osteoclast dynamic balance, but further research is needed to elucidate the exact mechanisms.…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…Hence, a clear understanding of the pathogenesis of OP requires a complete dissection and testing of the differentiation process of BMSCs. The differentiation of BMSCs into osteoblasts is regulated by several transcription factors, such as IGF-1, Osterix, Runx2 and others (9)(10)(11)(12). It is essential to understand how these factors regulate the differentiation of BMSCs towards osteoblasts and their function in the development of drugs for the treatment of OP and inflammatory bone diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have attempted to explain the pathogenesis of OP via different basic research methods and identify therapeutic targets by proteomic and metabonomic investigation of the pathogenic mechanism of OP. Previous studies [ 8 – 12 ] have shown that a variety of signaling pathways, such as the ER pathway, OPG/RANKL pathway, BMP-2/Smad pathway, classical Wnt/β-catenin signaling pathway, and PI3K/akt signaling pathway, can affect osteoblast proliferation and inhibit osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 99%